International Law and National Legislation Approaches in Addressing Ethnic Minority Discrimination in Indonesian - Susilo, Joko; Mubarrok, Muhammad Zaki (Generate Digital Publishing, 2025)
Objective: This study aims to explore discrimination against ethnic minorities in Indonesia and evaluate the effectiveness of international and domestic legal frameworks. It also identifies gaps between law and social practice and provides recommendations for strengthening regulations on the protection of ethnic minorities in Indonesia. Research Design & Methods: This study uses a normative juridical approach to analyze legal norms, regulations, international conventions, legal doctrines, national laws, court decisions, and the implementation of ICERD in Indonesia, and identifies challenges in the protection of ethnic minorities. Findings: This study shows that although Indonesia has ratified international conventions and passed laws on the protection of ethnic minorities, there is still a gap between the law and its implementation. Discrimination against minority groups such as Chinese, Papuans, and religious minorities continues, with challenges in integrating the international human rights framework and the need to raise awareness of the rights of ethnic minorities. Implications & Recommendations: This study will propose recommendations to strengthen legal protection for ethnic minorities in Indonesia, including by strengthening the legal framework, law enforcement, awareness campaigns, regular policy evaluations, and collaboration between government, civil society, and international bodies. Contribution & Value Added: This research will contribute to understanding the challenges of legal protection for ethnic minorities in Indonesia, provide policy recommendations, and raise awareness of gaps in the implementation and integration of international legal frameworks at the national level.